Parental perceptions, attitudes, and practices regarding their children's oral health in Kerala, India - A cross-Sectional study - Pooja Latti; Deepa Ramesan; Subramaniam Ramanarayanan (Wolters Kluwer Medknow Publications, 2022)
Introduction: Oral diseases in children, if left untreated can frequently lead to significant pain, interference with talking, eating, loss of school hours, and general health problems. Parents have an important role to play in the initiation and reinforcement of oral health-related behaviors for preventing and controlling oral diseases. Parental attitudes and perceptions have a direct influence on their children's oral health. The survey was conducted to investigate the parental perceptions, attitudes, and practices regarding their child's oral health. Methodology: A cross-sectional questionnaire-based survey was conducted among parents of primary school students (two government and two private) in Paravur town of Ernakulam district, Kerala. Data collection was done during the Parents-Teachers Association meeting. The prevalidated questionnaire, translated into local language Malayalam, consisted of 12 questions assessing the parental attitude and practice toward oral health and dental treatment. The data were tabulated and analyzed with Chi-square test. Results: The final sample comprised 414 parents; 105 men and 309 women. Less than 30% of the participants had taken their child for a dental visit in the past year. Over 43% had visited the dentist for treatment of decayed teeth. More than 53% of the parents reported that their children brushed their teeth twice daily. More than 93% agreed to supervise their child's brushing. About 30% of the parents are willing for routine dental checkups for their children more than three times a year. About 30% select the toothpaste and toothbrush as per recommendations from the dentist. Over 78% considered consulting a dentist as the first response to a dental complaint of the child. Conclusions: The study showed a positive attitude and perception of parents regarding the oral health of children in terms of money, time, and dental clinic visits.